Law on Asset Recovery for Corruption in Indonesia: An Urgent Need - Sekar Langit Jatu Pamungkas; Kuswardani (Rechtsidee, 2021)
Corruption is an organized crime, so that its existence is required to complete the law not only for the perpetrators but also for the results of acts of corruption which are often not found with a track record of all assets of corruption. This study aims to examine legal products in Indonesia regarding the seizure of assets resulting from criminal acts of corruption. Philosophically, the existence of criminal acts of corruption is a form of state responsibility to eradicate because there is not yet a strong legal basis to regulate the mechanism of confiscation effectively in the enforcement of corruption. This research method uses normative juridical with conceptual legal approach with qualitative descriptive research type. The results of this study can be concluded that the urgency of the establishment of the Draft Law on the confiscation of assets resulting from acts of corruption is to change the legal paradigm in law enforcement of criminal acts of corruption which is not only focused on perpetrators of corruption but assets resulting from criminal acts of corruption can be returned based on the amount of losses suffered by the perpetrators of corruption. country. The effectiveness of the law with the formation of these legal products closes the gaps that have so far arisen so that it triggers the existence of criminal acts of corruption.